On Quaternion Gaussian Bronze Fibonacci Numbers - Catarino Paula; Ricardo Sandra (Annales Mathematicae Silesianae, 2022)
In the present work, a new sequence of quaternions related to the Gaussian Bronze numbers is defined and studied. Binet’s formula, generating function and certain properties and identities are provided. Tridiagonal matrices are considered to determine the general term of this sequence.